El Bonaerense - Trapero, Pablo; Nieto, Guillermo; Román, Jorge; Ardú, Mimí; Levy, Darío (Optimum, 2004)
Shot on the cheap in Argentina, where the country's economic collapse has fuelled a new wave of rough-and-ready film productions, Pablo Trapero's "El Bonaerense" is an unflinching vision of moral cowardice, corruption and brutality in the ranks of the Buenos Aires police force. The "Bonaerense" of the title is country locksmith Zapa whose ex-police chief uncle gets him a job with the city's boys in blue after he runs into trouble in his provincial town (in Argentina, a Bonaerense is both someone who lives in the provinces around the capital and a slang term for the city's police officers). It's hardly an auspicious start for a career in law enforcement, but once he's sworn in, Zapa realises that everyone with a badge on the streets of Buenos Aires is an even bigger crook than he is. Falling in with dubious police inspector Gallo, Zapa uncovers a lawless world in which trigger-happy, racist drunks patrol the streets, protecting and serving only themselves. The follow-up to Trapero's accomplished "Mundo Grúa" (Crane World), "El Bonaerense" is a gritty urban policier shot in a cinema-verité style straight out of "Cops", and with much the same lack of objective commentary. Following his passive hero through the city, Trapero refrains from making any sweeping judgements about the onscreen action, yet it's clear that underneath the detached, ironic air burns a passionate sense of outrage at the institutionalised corruption and casual violence. [www.bbc.co.uk]